2020
DOI: 10.7150/thno.45363
|View full text |Cite
|
Sign up to set email alerts
|

Mcl-1 inhibition overcomes intrinsic and acquired Regorafenib resistance in Colorectal Cancer

Abstract: Intrinsic and acquired resistance to targeted therapies is a significant clinical problem in cancer. We previously showed that resistance to regorafenib, a multi-kinase inhibitor for treating colorectal cancer (CRC) patients, can be caused by mutations in the tumor suppressor FBW7 , which block degradation of the pro-survival Bcl-2 family protein Mcl-1. We tested if Mcl-1 inhibition can be used to develop a precision combination therapy for overcoming regorafenib resistance. M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
39
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 43 publications
1
39
0
Order By: Relevance
“…Decreased degradation of MCL-1 is involved in the E3 ubiquitin ligase FBW7 mutation-induced resistance to regorafenib in colorectal cancer patients [ 144 ]. The MCL-1 inhibitor S63845, AZD5991, AMG-176 restore sensitivity to regorafenib in FBW7 mutant colorectal cancer cells by restoring the apoptotic response [ 145 ]. In BRAF V600E -mutant colorectal cancer, mutant BRAF upregulates MCL-1 to confer apoptosis resistance [ 146 ].…”
Section: Introductionmentioning
confidence: 99%
“…Decreased degradation of MCL-1 is involved in the E3 ubiquitin ligase FBW7 mutation-induced resistance to regorafenib in colorectal cancer patients [ 144 ]. The MCL-1 inhibitor S63845, AZD5991, AMG-176 restore sensitivity to regorafenib in FBW7 mutant colorectal cancer cells by restoring the apoptotic response [ 145 ]. In BRAF V600E -mutant colorectal cancer, mutant BRAF upregulates MCL-1 to confer apoptosis resistance [ 146 ].…”
Section: Introductionmentioning
confidence: 99%
“…Myeloid cell leukemia 1 (MCL-1), an antiapoptotic B-cell lymphoma 2 (Bcl-2) family protein, blocks intrinsic pathway-initiated apoptosis by interfering with BAX–BAK interaction. The increased expression of MCL-1 has been observed in human cancers and has been associated with the induction of resistance to chemo-radiotherapy and targeting therapy [ 32 , 33 , 34 ]. The inhibition of MCL-1 expression has been indicated to reverse regorafenib resistance in CRC cells through the restoration of regorafenib-induced apoptosis [ 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…The increased expression of MCL-1 has been observed in human cancers and has been associated with the induction of resistance to chemo-radiotherapy and targeting therapy [ 32 , 33 , 34 ]. The inhibition of MCL-1 expression has been indicated to reverse regorafenib resistance in CRC cells through the restoration of regorafenib-induced apoptosis [ 34 ]. Our data showed that siMCL-1 effectively enhanced the regorafenib-mediated inhibition of the growth of HCC cells ( Figure 2 H,I).…”
Section: Discussionmentioning
confidence: 99%
“…By interaction with the proapoptotic proteins such as Bak or Bax, Mcl-1 is able to disrupt the mitochondrial membrane and ultimately prevents apoptosis [ 17 ]. Mcl-1 is frequently overexpressed in various cancers including ESCC [ 29 , 30 ], and it protects tumor cells from apoptosis induced by chemotherapeutic agents, such as cytarabine, daunorubicin, and regorafenib [ 31 , 32 ]. Knockdown of Mcl-1 by shRNA or selective inhibitor UMI-77 greatly enhances the sensitivity of ESCC cells to CDDP [ 33 ].…”
Section: Discussionmentioning
confidence: 99%